Instructional Management Based on the Think-Talk-Write Model to Enhance Students' Critical Thinking Skills - Hasiyatiningsih, Hasiyatiningsih (Journal of Educational Management Research, 2025)
Evaluating the performance of construction consultants is crucial to the success of a project, particularly in ensuring adherence to quality, budget, and timeline.  To examine the factors influencing stakeholder satisfaction, this study combines Importance-Performance Analysis (IPA) with SmartPLS-based Partial Least Squares Structural Equation Modeling (PLS-SEM).  A poll of respondents with prior experience in building projects was used to gather data.  The findings indicate that, although the constructed structural model is reasonably solid (R² = 0.790), factors such as professionalism, communication, quality control, project management, and support have not demonstrated a significant impact on the perceived significance of the consultant’s job.  This result implies that data-driven performance improvement techniques are required to enhance consultants’ involvement in building projects. The findings of this study highlight the importance of integrating data-driven performance improvement techniques into educational programs for construction management. By emphasizing professionalism, communication, project management, and quality control, educational institutions can better prepare future construction consultants to meet stakeholder expectations and improve their contributions to building projects.